2012
DOI: 10.1029/2012jc008364
|View full text |Cite
|
Sign up to set email alerts
|

Inferring dynamics from the wavenumber spectra of an eddying global ocean model with embedded tides

Abstract: .[1] The slopes of the wavenumber spectra of sea surface height (SSH) and kinetic energy (KE) have been used to infer "interior" or surface quasi-geostrophic (QG or SQG) dynamics of the ocean. However, inspection of spectral slopes for altimeter SSH in the mesoscale band of 70 to 250 km shows much flatter slopes than the QG or SQG predictions over most of the ocean. Comparison of altimeter wavenumber spectra with spectra from an eddy resolving global ocean circulation model (the HYbrid Coordinate Ocean Model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(149 citation statements)
references
References 38 publications
14
135
0
Order By: Relevance
“…One possible explanation is that Xu and Fu's estimates, despite the attempt to remove instrumental noise, are still contaminated by noise at scales that are only marginally resolved by altimeters. This was corroborated by the modeling results of Sasaki and Klein (2012) and Richman et al (2012), who found steeper spectra than the altimetric ones in regions of low mesoscale activity. A second possibility is that ageostrophic flows, like internal tides, have an important signature in SSH, so that velocities inferred from SSH using geostrophic balance are not accurate .…”
Section: Altimetry Observationssupporting
confidence: 77%
See 2 more Smart Citations
“…One possible explanation is that Xu and Fu's estimates, despite the attempt to remove instrumental noise, are still contaminated by noise at scales that are only marginally resolved by altimeters. This was corroborated by the modeling results of Sasaki and Klein (2012) and Richman et al (2012), who found steeper spectra than the altimetric ones in regions of low mesoscale activity. A second possibility is that ageostrophic flows, like internal tides, have an important signature in SSH, so that velocities inferred from SSH using geostrophic balance are not accurate .…”
Section: Altimetry Observationssupporting
confidence: 77%
“…Using model output provided by Richman et al, we find that internal tides do indeed dominate the kinetic energy at scales of order 100 km in the region under consideration here. Richman et al (2012) also found that the peaks due to internal tides are considerably broadened, which, together with the superposition with subinertial energy, could explain why no distinct peaks are apparent in the observed spectra.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Altimetric observations and high-resolution simulations show that baroclinic tides appear as somewhat broadened peaks in wavenumber spectra, to the extent that they may be better described as broad-band signals (e.g., Ray and Mitchum 1997;Zhao et al 2012;Richman et al 2012). A theory that explains this signature in wavenumber spectra is lacking and in situ observations are difficult because of the tides' large spatial scales and high frequencies.…”
Section: Tidesmentioning
confidence: 99%
“…Le . and Richman et al (2012) recently pointed out the role of internal tides that could explain the flatter slopes.…”
Section: P Y Le Traon: From Satellite Altimetry To Argo and Operatimentioning
confidence: 99%